Effects of heat sink on frictional heat effect in PEEK/Steel Pair（Numerical calculation using OpenFOAM model and experiments） - Takuma KOGAWA; Naoto OGASAWARA; Daisuke MORI; Tomoharu AKAGAKI (Nihon Kikai Gakkai ronbunshu, 2019)
The PEEK material has been applied to a sliding bearing system in a power plant system because of its high mechanical durability. In the solid friction of the PEEK materials, the frictional heat becomes the important factor because the temperature increasing due to the frictional heat causes the rapidly increasing of the frictional coefficient of the specimen. In order to maintain the low frictional coefficient of the PEEK materials, the effective cooling method for the PEEK materials needs to be developed. In this study, the passive cooling method, which attaches the heat sink to the PEEK materials, was suggested. For evaluating the suggested cooling method of the PEEK materials, the calculation model adopting OpenFOAM, which is the open source software, has been developed. Adopting some functions and library of OpenFOAM, the frictional heat, heat resistance, and heat transfer coefficient on the heat sink were modeled. The sliding bearing experiment was conducted and time variation of the temperature and friction coefficient in the ring specimen were measured. The temperature variation in the ring specimen was compared with the calculation result. From the numerical calculation results, the developed calculation model could simulate the temperature time variation of the ring obtained in the experiment, when variation of the frictional coefficient, heat resistance, and heat transfer coefficient were modeled appropriately. Finally, the calculation predict ability using OpenFOAM in the considered situation was evaluated.